1985
DOI: 10.1128/jb.162.2.611-614.1985
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lipoglycans in ureaplasmas

Abstract: Serotypes 3, 4, and 8 of Ureaplasma urealyticum were found to contain lipoglycans. Although the ratios of their components differed, all contained neutral sugars, fatty acids, glycerol, and phosphorus. All three became labeled when the organisms were cultivated in the presence of [14C]glucose, [14C]palmitic or [14C]oleic acids, and inorganic 32p. Only neutral sugars were found, and these consisted of mannose, glucose, and galactose. Hot phenol extracts of uninoculated and supernatant culture media contained po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Ureaplasma may activate the complement system in situ. Ureaplasm a lipoglycans consist of mannose residues 26 . Benstein et al 27 reported Ureaplasma parvum attached to mannose‐binding lectin.…”
Section: Discussionmentioning
confidence: 99%
“…Ureaplasma may activate the complement system in situ. Ureaplasm a lipoglycans consist of mannose residues 26 . Benstein et al 27 reported Ureaplasma parvum attached to mannose‐binding lectin.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence support this view: 1) a low amniotic fluid glucose concentration is a well-established biomarker of IAI. [134][135][136][137] Low glucose concentrations are also associated with microbial invasion of other biological fluids including cerebrospinal [138,139] and synovial fluid; [140] 2) Fusobacterium species contain a galactose-binding protein, and it is possible that this protein may contribute to the decrease concentrations of galactose in infected amniotic fluid; [141] 3) Ureaplasmal lipoglycans are constituted primarily of mannose, glucose, and galactose, [142] suggesting that these carbohydrates may be consumed with the replication of this microorganism in the amniotic fluid; and 4) glucose is also required as a fuel by activated neutrophils engaged in the process of microbial phagocytosis and killing. [143] Methyladenine was the most important classifier as determined by Random Forest analysis (Gini Index).…”
Section: Principal Findings Of the Studymentioning
confidence: 99%
“…In preliminary experiments using a standard procedure for lipoglycan purification (Smith, 1985(Smith, , 1992 no glycoconjugate could be extracted from M. penetrans cells with hot phenol after removal of lipids. All the glycosylated material was found in the methanol/ chloroform phase used for removal of lipids (data not shown).…”
Section: Identification Of a Glycolipid Fraction From M Penetransmentioning
confidence: 99%